A Case of Renal Inflammatory Pseudotumor Leading to Nephrectomy. (March 2021) - Tuan Linh, Le; Minh Duc, Nguyen; Tra My, Thieu-Thi; Nhan Hien, Phan; Ngoc Minh, Tran; Van Lenh, Bui
Inflammatory pseudotumor (IPT) of the kidney is a rare benign disorder with unknown etiology. In IPT patients, some nonspecific symptoms might present, such as fever, hematuria, and back pain. As it can appear on computed tomography and magnetic resonance imaging as a hypovascular mass with surrounding fat stranding, IPT can be misdiagnosed as a primary tumor. Since the clinical symptoms, radiographic features, and preoperative findings can be inconsistent, it is imperative to confirm IPT based on histopathological assessment. In the present study, we describe a case of renal IPT in a 13-year-old girl. The patient was treated with nephrectomy of the right kidney since the preoperative diagnosis was renal carcinoma. Pathological examination revealed an IPT. This article emphasizes the importance of preoperative definitive diagnosis in avoiding unnecessary nephrectomy.